PENGARUH CELEBRITY ENDORSMENT, VARIASI PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN CASE HANDPHONE DI INSTAGRAM ANYACOLECTION - Agustina, Ayu; Fusfita, Nurlia; Novriza, Eri (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to examine the effect of celebrity endorsements, product variety, and product quality on the decision to purchase a mobile phone case at anyacollection_. The population and sample used in this study were coustemers from the anyacolection_ online shop who had bought cell phone case products at anyacolection_. Data collection was carried out by distributing questionnaires with Likert scale measurements. Then, the data testing techniques used in this study were validity and reliability tests, R-Squer tests, and hypothesis testing through bootstrapping using Smart PLS 3.0 software. The results showed that celebrity endorsements and product quality had a positive and significant effect on purchasing decisions, while product variations had a negative effect on purchasing decisions. The better the promotion and the level of product quality, the more it will influence the decision to buy a cellphone case at the anyacollection_ online shop